Accuracy of Fine Needle Aspiration Biopsy (F.N.A.B) in Diagnosis of Breast Lump - Abedalrahman, Sarab K. (AL-Kindy College Medical Journal, 2020)
Background: Breast cancer is the first one among Iraqi females. Most of them present later for diagnosis. Early detection center in tertiary hospital practice uses FNAB for early diagnosis. Publications on accuracy of this detection are scarce. Objective: To test the accuracy of FNAB in breast lump diagnosis. Methods: Diagnostic test accuracy study, on 204 women with breast lump, attending the oncology department in 2017. Results: Fine-needle aspiration biopsy diagnosis of histologically malignant cases were, malignant in 89 (87.3%), suspicious of malignancy in 5 (4.9%), and benign in 4 (3.9%). Complete sensitivity was 87.3%, and specificity was 100%, with 12.7% false negative results and no false positive cases. The accuracy was 94%.